A Model for Community-Based Pediatric Oral Heath: Implementation of an Infant Oral Care Program - Francisco J. Ramos-Gomez (International Journal of Dentistry)
The Affordable Care Act (ACA) mandates risk assessments, preventive care, and evaluations based on outcomes. ACA compliance will require easily accessible, cost-effective care models that are flexible and simple to establish. UCLA has developed an Infant Oral Care Program (IOCP) in partnership with community-based organizations that is an intervention model providing culturally competent perinatal and infant oral care for underserved, low-income, and/or minority children aged 0–5 and their caregivers. In collaboration with the Venice Family Clinic's Simms/Mann Health and Wellness Center, UCLA Pediatrics, Women, Infants, and Children (WIC), and Early Head Start and Head Start programs, the IOCP increases family-centered care access and promotes early utilization of dental services in nontraditional, primary care settings. Emphasizing disease prevention, management, and care that is sensitive to cultural, language, and oral health literacy challenges, IOCP patients achieve better oral health maintenance “in health” not in “disease modality”. IOCP uses interprofessional education to promote pediatric oral health across multiple disciplines and highlights the necessity for the “age-one visit”. This innovative clinical model facilitates early intervention and disease management. It sets a new standard of minimally invasive dental care that is widely available and prevention focused, with high retention rates due to strong collaborations with the community-based organizations serving these vulnerable, high-risk children.